CONCEPTS AND BASIS OF INTERNATIONAL RELATIONSHIPS IN THE PERSPECTIVE OF ISLAMIC GOVERNMENT - Zarul Arifin Sri Sudono Saliro (Prodi Tata Negara (Siyasah) IAIN Langsa, 2021)
After Islam was spread by the Muslims throughout the universe, the contact of the Muslims with the a'jam nations had entered a new phase in international relations. Territorial boundaries that are displayed in plain sight do not make Muslims limit themselves in interactions between nations. The relationship that occurs between Muslims and other nations is inspired by the teachings of Islam itself which requires Muslims to always maintain peace between Muslims and internal and external Muslims. Islam has laid the foundation for peace in international relations with a basic stipulation that Muslims are not justified even if they interfere with the internal affairs of other nations